Green Synthesis of pH-Responsive, Self-Assembled, Novel Polysaccharide Composite Hydrogel and Its Application in Selective Capture of Cationic/Anionic Dyes - Srivastava, Nandita; Roy Choudhury, Anirban (Frontiers in Chemistry, 2021)
Dyes are one of the most hazardous chemicals causing significant environmental pollution and affecting water quality. Majority of the existing methods for dye removal and degradation involve synthetic membranes and use of hazardous chemicals, further resulting in secondary pollution. The present study reports polysaccharide based novel composite hydrogel as biodegradable matrix for pH-responsive selective adsorption of cationic/anionic dyes. This membrane showed pH-responsive adsorption of methyl green (MG) and methyl orange (MO) with similar adsorption equilibrium i.e., 315 mg g-1 and 276 mg g-1, respectively. Interestingly, selective adsorption at different pH has allowed separation of dye mixtures that holds incredible industrial importance for dyes recovery. The hydrogel matrix was able to completely separate MG, a model cationic dye at neutral pH from the dye mixture whereas, it was possible to remove 60% MO, a model anionic dye at acidic pH. Furthermore, comprehensive isothermal and kinetic studies of adsorption revealed that Freundlich isotherm describing the multilayer coverage and pseudo-second-order kinetics were followed. Thermodynamic studies indicated that the adsorption process was spontaneous and endothermic. In fact, the membrane was reusable for at least ten cycles and exhibited desorption efficiency of 80% and 60% for MO and MG respectively, which may be further recycled to make the process environmentally sustainable. Overall, this study proposes an inexpensive, simple, biologically safe, and efficient adsorbent material for dye effluent treatment.